2019
DOI: 10.1007/s10921-019-0636-z
|View full text |Cite
|
Sign up to set email alerts
|

Barkhausen Noise Probes and Modelling: A Review

Abstract: This review looks at the main types of magnetic Barkhausen noise (BN) probes that have been developed. The aim of this review is to summarize the existing knowledge of magnetic Barkhausen noise probes and the magnetic modelling of them. The BN probes have been the focus of many previous studies, but no sufficient review or conclusions have been made so far. This review focuses on combining information regarding the different types of BN probes and their modelling. The review is divided into two sections; in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…1,2 The analysis of the Barkhausen noise has emerged as a valuable technique for studying the dynamics of domain formation and domain wall motion in ferromagnets. 3,4 The similar effect representing the appearance of the Barkhausen pulses (BPs) in ferroelectrics was discovered in Rochelle salt 5 and was later studied in potassium dihydrogen phosphate, 6,7 barium titanate, [8][9][10] lithium niobate, 11 gadolinium molybdate, 12,13 and lithium tantalate crystals. 14 BPs manifest themselves as the sharp peaks in the switching current during the application of a constant or slow-varying external electric field.…”
mentioning
confidence: 83%
“…1,2 The analysis of the Barkhausen noise has emerged as a valuable technique for studying the dynamics of domain formation and domain wall motion in ferromagnets. 3,4 The similar effect representing the appearance of the Barkhausen pulses (BPs) in ferroelectrics was discovered in Rochelle salt 5 and was later studied in potassium dihydrogen phosphate, 6,7 barium titanate, [8][9][10] lithium niobate, 11 gadolinium molybdate, 12,13 and lithium tantalate crystals. 14 BPs manifest themselves as the sharp peaks in the switching current during the application of a constant or slow-varying external electric field.…”
mentioning
confidence: 83%
“…The ideal way to observe this mechanism is through the so-called Magnetic Barkhausen Noise (MBN) technique [ 27 ]. Domain wall motions generate local flux variations that trigger discontinuous magnetic flux density displayed as a series of electrical pulses induced in an inductive magnetic sensor [ 28 ]. The domain number is vast, the wall motions can be assimilated to a stochastic process, and the MBN raw signal is erratic and not reproducible.…”
Section: The Magnetization Mechanisms: Definitionmentioning
confidence: 99%
“…For low-frequency BHN measurements near the surface, it was shown that in case-carburized steel, the residual stresses change differently compared to the subsurface in response to the prior applied tensile or compressive stresses [18]. Although BHN has been the subject of numerous studies, the results are difficult to compare because most studies differ in terms of the material and samples used [19]. Therefore, it can be concluded that a better understanding of how different factors influence BHN is still needed.…”
Section: State Of the Artmentioning
confidence: 99%